Deskripsi Preferensi Risiko dan Partisipasi Petani Dalam Asuransi Tanaman Padi di Desa Simpang Datuk Kecamatan Nipah Panjang Kabupaten Tanjung Jabung Timur - Zainuddin Zainuddin; Fitri Rahmadita; Siti Abir Wulandari (Jurnal MeA (Media Agribisnis), 2023)
The research was conducted in Simpang Datuk Village, Nipah Panjang District, East Tanjung Jabung Regency with the aim of describing rice farmers' risk preferences, and the factors that determine farmers' participation in rice crop insurance (AUTP). The research method was conducted by survey. The research sample consisted of 20 farmers who took rice farming insurance (AUTP) and 43 farmers who did not take AUTP insurance from a population of 430 farmers. The method of analysis through simplification and tabulation is carried out, and logit regression is used to look at the factors that influence rice farmers to take rice farming insurance (AUTP). In general, rice farmers in Simpang Datuk Village have a risk averse preference. The risk preferences of farmers participating in AUTP are risk averse, while farmers who are not participating in AUTP show that they are not risk averse (risk takers). The variables of farmer age, duration of rice farming, and risk preferences significantly influence farmers' decisions to participate in the rice crop insurance program (AUTP) in Simpang Datuk Village, Nipah Panjang District, East Tanjung Jabung Regency.